Improvement in d-xylose utilization and isobutanol production in S. cerevisiae by adaptive laboratory evolution and rational engineering - Promdonkoy, Peerada; Mhuantong, Wuttichai; Champreda, Verawat; Tanapongpipat, Sutipa; Runguphan, Weerawat (Journal of industrial microbiology & biotechnology, 2020)
Abstract As the effects of climate change become apparent, metabolic engineers and synthetic biologists are exploring sustainable sources for transportation fuels. The design and engineering of microorganisms to produce gasoline, diesel, and jet fuel compounds from renewable feedstocks can significantly reduce our dependence on fossil fuels as well as lower the emissions of greenhouse gases. Over the past 2 decades, a considerable amount of work has led to the development of microbial strains for the production of advanced fuel compounds from both C5 and C6 sugars. In this work, we combined two strategies—adaptive laboratory evolution and rational metabolic engineering—to improve the yeast Saccharomyces cerevisiae’s ability to utilize d-xylose, a major C5 sugar in biomass, and produce the advanced biofuel isobutanol. Whole genome resequencing of several evolved strains followed by reverse engineering identified two single nucleotide mutations, one in CCR4 and another in TIF1, that improved the yeast’s specific growth rate by 23% and 14%, respectively. Neither one of these genes has previously been implicated to play a role in utilization of d-xylose. Fine-tuning the expression levels of the bottleneck enzymes in the isobutanol pathway further improved the evolved strain’s isobutanol titer to 92.9 ± 4.4 mg/L (specific isobutanol production of 50.2 ± 2.6 mg/g DCW), a 90% improvement in titer and a 110% improvement in specific production over the non-evolved strain. We hope that our work will set the stage for an economic route to the advanced biofuel isobutanol and enable efficient utilization of xylose-containing biomass.